Consuming hunger [videorecording] part 1 - getting the story.
If the Vietnam conflict was a television war then the starvation in Ethiopia was "television famine." Our thoughts and feelings about it and responses to it have been completely shaped by television images. Consuming Hunger analyzes how these images became our reality.